Development and psychometric evaluation of Sexual and Reproductive Health Assessment Scale for women with educable intellectual disability (SRH-WIDS): a sequential exploratory mixed-method study - Abbas Ebadi; Ziba Taghizadeh; Maryam Farmahini Farahani (BMC, 2022)
Abstract Background Women with Intellectual disability have many problems in their sexual and reproductive health due to their special mental and physical conditions caused by disability. This study aimed to develop and evaluate the psychometric properties of Sexual and Reproductive Health Scale for Women with Educable Intellectual disability. Methods This sequential exploratory mixed-method study was conducted at two qualitative and quantitative stages in Tehran, from 2018 to 2020. At the qualitative stage, in-depth and semi-structured interviews were conducted with 21 parents and caregivers of women with intellectual disability to explain the concepts and to generate items. Thereafter, the item pool was formed based on the concepts and themes extracted from the qualitative phase as well as the review of literature. At the second stage, psychometric properties of the scale were assessed. Finally, responsiveness, interpretability, and feasibility of the scale were determined. Results An item pool containing 95 items was produced at the first stage. At the second stage, the final version of scale was developed. The psychometric properties of this final version were then assessed and the results showed that the instrument has good validity and reliability. The results of exploratory factory analysis showed that the instrument contains seven factors. Accordingly, these factors explained 53% of the total variance of the instrument variables. Conclusions The results show that the SRH-WIDS with 25 items has sufficient validity and reliability, so it could be easily used by caregivers to assess the sexual and reproductive health of Women with Educable Intellectual disability. Ethical code: IRI.TUMS.VCR.REC 1397.340.